Unilateral Silent Neonatal Testicular Torsion: A Case Report - Ali Jawad; Hiba Hamdar; Najib Hamad; Andrea Eid; Noama Husseini; Ahmad Atieh; Abbas Al Bazzal; Mohammad Ali Mtairek (Pediatric Sciences Journal)
Neonatal testicular torsion is a critical urological emergency that poses a unique diagnostic challenge. It needs a high index of suspicion in a neonate with vague symptoms. It is characterized by the axial rotation of spermatic cord structures, which results in interruption of blood supply to the testicle. The duration of symptoms and degree of twisting have an impact on the viability of the testis, emphasizing the importance of prompt diagnosis and management. We report a 1 day-old neonate who presented by acute scrotum syndrome, with tenderness, hardness, edema, and erythema of the left scrotum. The neonate was afebrile with normal stool passage and without any constitutional symptoms. The neonate was delivered via cesarean section after an uneventful pregnancy. Diagnostic ultrasound revealed an increase in left testicular volume, a markedly heterogeneous structure, and an irregular outline which were considered signs of left testicular torsion. In addition, color Doppler imaging showed the absence of vascularization within the parenchyma, prompting urgent surgery. During surgery, the left testis was found black with no blood supply, so no detorsion was done and the patient underwent an orchidectomy for his left testis. Besides, sympathetic orchidopathia of right testicle was present as edema and redness. Following surgery, a comprehensive approach included a nil per os (NPO) regimen, intravenous fluids, amoxicillin- clavulanic acid, and paracetamol. The neonate was symptom free and discharged on the third day of life. This case highlights that axial torsion can present late as a surgical emergency in the first day of life and emphasizes the need for high index of suspicion in diagnosis and for a prompt multidisciplinary cooperation and intervention to prevent irreversible ischemic damage.